1999
DOI: 10.1021/la9900775
|View full text |Cite
|
Sign up to set email alerts
|

Protection of a Decapeptide from Proteolytic Cleavage by Lipidation and Self-Assembly into High-Axial-Ratio Microstructures:  A Kinetic and Structural Study

Abstract: We report on the synthesis, kinetics of proteolysis by trypsin, and morphological characterization of a novel lipidated decapeptide that spontaneously self-assembles in aqueous solutions into 0.5 μm diameter hollow tubules and helices that range in length from tens to hundreds of micrometers depending on formation conditions. We also report on an improved method for the tritioacetylation of peptides. Tight molecular packing of the peptide−amphiphile into a crystalline bilayer array forces tight packing between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Compound 3 (Fig. 4a) formed hollow tubules or helical ribbons spontaneously; these self-assembled structures protected compound 3 from trypsin degradation [65]. Several reviews describing selfassembly mechanisms, compositions and applications of lipidated peptides were available [84,[101][102][103][104].…”
Section: Oligomers and Self-assembling Macromoleculesmentioning
confidence: 99%
“…Compound 3 (Fig. 4a) formed hollow tubules or helical ribbons spontaneously; these self-assembled structures protected compound 3 from trypsin degradation [65]. Several reviews describing selfassembly mechanisms, compositions and applications of lipidated peptides were available [84,[101][102][103][104].…”
Section: Oligomers and Self-assembling Macromoleculesmentioning
confidence: 99%
“…They have been shown capable of delivering biologically active peptides for a variety of applications including angiogenesis (19,20), osteogenesis (21,22), neurogenesis (23,24), atherosclerosis treatment (25), cancer therapy (26,27), and islet transplantation (28,29). Also, peptide amphiphile micelles are comprised of a high concentration of peptide (30), inhibit peptide degradation (31), and can greatly increase peptide intracellular delivery (32). Recent research by the Tirrell Group has shown that peptide amphiphile micelles that display a tumor-specific cytotoxic T cell epitope can function as a self-adjuvanting vaccine delivery system capable of inducing a tumor-suppressing immune response when given prophylactically (33).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic materials that self-assemble with nanometer-scale features from polypeptides, [1][2][3] oligopeptides, [4][5][6] cyclic peptides, [7] and peptide amphiphiles [8][9][10] may contribute to regenerative medicine as scaffolds that mimic the complex architecture and biochemical functionality of native extracellular tissue. Our laboratory has previously reported on peptide amphiphile molecules (PAs) that self-assemble from aqueous media into three-dimensional networks of bioactive nanofibers.…”
Section: Introductionmentioning
confidence: 99%